Kolaborasi Aktor dalam Ekosistem Wirausaha Pertanian (Sebuah Pengalaman pada Petani Muda Hortikultura di Jawa Barat) - Mukti, Gema Wibawa; Charina, Anne; Kusumo, Rani Andriani Budi (Universitas Galuh, 2025)
This paper aims to study the collaboration between actors in the horticultural agricultural entrepreneurship ecosystem in West Java. The research method used in this paper is descriptive - qualitative analysis, with the focus of analysis on the quadruple helix collaboration between farming actors, government, universities and the agricultural industry, analyzing the knowledge transfer process carried out among the actors involved, to develop agricultural entrepreneurship. The results explain that strengthening human resources and agricultural institutions are the main aspects in creating a competitive and productive agricultural entrepreneurship ecosystem. In its implementation, the programs have helped farmers in the development of farming, both in terms of onfarm cultivation and farm management. But on the other hand, the implementation of the program in the field is still limited and not sustainable. To overcome this, synergistic collaboration is needed among the actors involved (government, universities, industry and farming actors). Information disclosure and intense communication can help the synergy process, so that the actors involved can strengthen each other, facilitating the achievement of activity outcomes, namely creating a conducive, productive and competitive agricultural entrepreneurship ecosystem.